Розв’язання задачі про згин пластини методом скінченних елементів з використанням сплайнів п'ятого степеня на трикутній сітці - Литвин, О.М.; Томанова, І.С. (Проблемы машиностроения, 2017)
Розглянуто використання сплайнів 5-го степеня на трикутній сітці вузлів для розв’язання задачі про згин для жорстко защемленої пластини з рівномірним навантаженням. Результати проведеного обчислювального експерименту порівнюються з відомими результатами вчених. Предложена схема решения бигармонической задачи для прямоугольной пластины в случае граничных условий, которые соответствуют условиям жесткого защемления пластины в виде сплайна 5-го степеня, который обеспечивает принадлежность приближенного решения класса . Рассмотрено применение формул для построения полинома пятого степеня бигармонической задачи. Проведен эксперимент, который сравнивает точное решение с полиномами, полученными на квадратной области. Эксперимент показал, чем больше разбиение области на треугольники, тем меньше погрешность. Splines are involved in a large number of physical processes. Using splines for research biharmonic problem is widely used in practice, particularly in the study of the deflection plates. Many exact solutions have been developed for isotropic linear elastic thin plates; most of them can be found in the monographs Tymoshenko (Tymoshenko and Woinowsky-Krieger, 1959). In this paper we propose a scheme for solving biharmonic problem for a rectangular plate in the case of boundary conditions that match the conditions of rigid support plate in the form of a spline of the 5th degree, which provides an approximate solution of a class affiliation These polynomials are not used previously for the biharmonic equation. The article was considered the application of the formulas for the construction of a polynomial of the fifth degree taken from [1] biharmonic problem. An experiment was conducted that compares the current solution with polynomials, which were obtained by the formulas [1] to the square area. As has been taken exact solutions formula (a) in work [3] on the field . The area was divided into two, four, eight triangles. The experiment showed greater than a partition area into triangles, the smaller the error.